2006
DOI: 10.1021/bm060120k
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for the C-Terminal Domain of A Dragline Spider Silk Protein in Directing Fiber Formation

Abstract: We have employed baculovirus-mediated expression of the recombinant A. diadematus spider dragline silk fibroin rADF-4 to explore the role of the evolutionary conserved C-terminal domain in self-assembly of the protein into fiber. In this unique system, polymerization of monomers occurs in the cytoplasm of living cells, giving rise to superfibers, which resemble some properties of the native dragline fibers that are synthesized by the spider using mechanical spinning. While the C-terminal containing rADF-4 self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 30 publications
(78 reference statements)
1
86
0
1
Order By: Relevance
“…We ( Huemmerich et al, 2004b) and subsequently others ( Huang et al, 2006, Ittah et al, 2007, Ittah et al, 2006, Lin et al, 2009and Stark et al, 2007 have shown the C-terminal NR domains to adopt a predominantly α-helical conformation in vitro. These domains have been postulated to form the outer layer of droplet-like structures observed in the spinning dope in vivo ( Jin and Kaplan, 2003, Lin et al, 2009and Vollrath and Knight, 1999.…”
Section: Introductionmentioning
confidence: 73%
“…We ( Huemmerich et al, 2004b) and subsequently others ( Huang et al, 2006, Ittah et al, 2007, Ittah et al, 2006, Lin et al, 2009and Stark et al, 2007 have shown the C-terminal NR domains to adopt a predominantly α-helical conformation in vitro. These domains have been postulated to form the outer layer of droplet-like structures observed in the spinning dope in vivo ( Jin and Kaplan, 2003, Lin et al, 2009and Vollrath and Knight, 1999.…”
Section: Introductionmentioning
confidence: 73%
“…The synthesis of the whole artificial gene appears to be a very complex problem, which will be solved during further experiments. Some authors (Jin and Kaplan 2003;Ittah et al 2006) suggested that hydrophilic N-and C-termini are necessary for nanofibril's and micelle's formation. Nevertheless, the proteins obtained from expression of the artificial genes that contain only the hydrophobic core regions possess all characteristic properties of the full-length spidroins.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic production in mammary glands and secretion into milk has been tried in mice [71] and goats [72], but the fairly low yields [7] do not justify the long development times and high production cost. Insects cells have proven to be important tools for the study of assembly properties of spidroin fragments in the cytoplasm [73,74], but these appear to be less suitable for large-scale production. Motivated by structural similarities between spider and silkworm silk, the expression of spidroins in cell lines and larvae of B. mori have been tried, with solubility as the primary limitation [75].…”
Section: Recombinant Spidroin Productionmentioning
confidence: 99%
“…Biochemical studies of recombinant ADF-3 and ADF-4 fragments that have been lyophilized, resolubilized in guanidinium thiocyanate and dialysed revealed that the presence of the non-repetitive C-terminal domain affects aggregation behaviour [78]. Upon expression in the cytosol of insect cells, ADF-4 fragments lacking the C-terminal domain do not self-assemble into nano fibers, as do their counterparts containing the C-terminal domain, but instead form aggregates [74]. The presence of amphipathic helices in the C-terminal domain has been proposed to be important for fibre formation [104].…”
Section: Structure and Function Of Spidroin Domainsmentioning
confidence: 99%
See 1 more Smart Citation